Detection and molecular characterization of VRE isolates in Slovakia from stool samples positive for Clostridioides difficile toxins - Kuzma, Jozef; Palcová, Lenka; Timko, Jaroslav; Bastová, Veronika; Janošcová, Veronika; Chmelař, Dittmar (Folia microbiologica, 2022)
The study aimed to identify colonized patients as a possible source of eventual VRE (vancomycin-resistant enterococci) infection from stool samples positive for glutamate dehydrogenase antigen, as well as for Clostridioides difficile toxins A and B. The study was carried out from 7/2020 to 9/2021. Stool samples were grown in a brain heart infusion medium with a gram-positive non-spore-forming bacteria supplement under aerobic conditions. The samples for VRE identification were grown on CHROMID® VRE agar, and the MICs for vancomycin and teicoplanin were also estimated. The presence of the vanA/vanB genes was tested using the PCR method. The total number of 113 stool samples positive for Clostridioides difficile toxins was analyzed. Of these samples, 44 isolates with VRE characters were identified. The most prevalent isolates in our set of isolates were Enterococcus faecium (27 isolates, 62%), Enterococcus faecalis (9 isolates, 21%), Enterococcus solitarius (4 isolates, 9%), Enterococcus durans (2 isolates, 4%), 1 isolate Enterococcus sulfurous (2%), and Enterococcus raffinosus (2%). In total, 26 isolates were detected in the study in the presence of vanA genes (24 isolates E. faecium, 2 isolates E. faecalis) and 18 isolates detected in the presence of vanB genes (7 isolates E. faecalis, 4 isolates E. solitarius, 3 isolates E. faecium, 2 isolates E. durans, 1 isolate E. sulfurous, and E. raffinosus). The results of this study showed the local dominance character of the vanA gene of hospital VRE isolates that were carriers of genes associated with high resistance to vancomycin, teicoplanin, and occasionally linezolid.
Keywords: Vancomycin; mikrobiální testy citlivosti; Humans; Slovenská republika; Gram-Positive Bacterial Infections; Enterococcus faecium; lidé; Vancomycin-Resistant Enterococci; Clostridioides difficile; Anti-Bacterial Agents; teikoplanin; bakteriální proteiny; Bacterial Proteins; enterokoky rezistentní vůči vankomycinu; Microbial Sensitivity Tests; Teicoplanin; Slovakia; antibakteriální látky; grampozitivní bakteriální infekce; vankomycin